RESPOSTAS ESTRUTURAIS DO XILEMA DE EUCALYPTUS ÀS DIFERENTES CONDIÇÕES HÍDRICAS - Silva, Ana Paula Camara da (2020)
Eucalyptus covers a wide range of naturally occurring species, which qualifies its genotypes to grow and develop in much of the world. In addition to having desirable anatomical characteristics for the already established and expanding paper and cellulose